Functional domain analysis of glass, a zinc-finger-containing transcription factor in Drosophila. - O'Neill, E M (1995)
The glass gene is required for proper photo-receptor differentiation during development of the Drosophila eye glass codes for a DNA-binding protein containing five zinc fingers that we show is a transcriptional activator. A comparison of the sequences of the glass genes from two species of Drosophila and a detailed functional domain analysis of the Drosophila melanogaster glass gene reveal that both the DNA-binding domain and the transcriptional-activation domain are highly conserved between the two species. Analysis of the DNA-binding domain of glass indicates that the three carboxyl-terminal zinc fingers alone are necessary and sufficient for DNA binding. We also show that a deletion mutant of glass containing only the DNA-binding domain can behave in a dominant-negative manner both in vivo and in a cell culture assay that measures transcriptional activation.